Experimental investigation of a plasma-covered cavity-backed slot antenna - Campbell, Thomas G.; Croswell, William F.; United States. National Aeronautics and Space Administration; Langley Research Center (Washington, D.C. : National Aeronautics and Space Administration ; [Springfield, Va. : For sale by the Clearinghouse for Federal Scientific and Technical Information, 1969)
Plasma covered cavity-backed slot antenna investigation.
Prepared at Langley Research Center.
"November 1969."
Cover title.
Includes bibliographical references (p. 9).
Mode of access: Internet.
Keywords: Radio -- Interference; Space vehicles -- Atmospheric entry; Space vehicles -- Radio antennas -- Testing; Plasma waveguides -- Testing; Aperture antennas -- Testing